Disputes Over General Election Results Based on Judicial Activism and Judicial Restrain in Realizing the Principles of Honest and Fair in General Elections - Anjas Rinaldi Siregar; Anna Erliyana (JURNAL PENDIDIKAN IPS, 2025)
The settlement of general election result disputes (PHPU) is a crucial issue in realizing honest and fair elections in Indonesia. The Constitutional Court, as the guardian of the constitution, often faces a dilemma between applying Judicial Activism and Judicial Restrain in adjudicating PHPU cases, particularly regarding structured, systematic, and massive (TSM) violations. This article aims to analyze the concepts, influencing factors, and implementation of Judicial Activism and Judicial Restrain within the Constitutional Court's practices, by examining key rulings including Decision No. 01/PHPU-PRES/XVII/2019. This study employs a normative legal method with statutory, case, and conceptual approaches. The results show an inconsistency in the Constitutional Court's application of Judicial Activism, especially concerning TSM violations, which are often regarded as beyond its authority. On the other hand, Judicial Restrain is frequently used as a justification to limit the Court's assessment of substantive justice in the electoral process. This article recommends the need for a proportional balance between Judicial Activism and Judicial Restrain, as well as strengthening the Constitutional Court's role in ensuring electoral justice to protect citizens' voting rights and the quality of democracy.